Incidence and Risk Factors for Seizures Associated with Deep Brain Stimulation Surgery. (16th November 2020) - Atchley, Travis; Elsayed, Galal; Sowers, Blake; Walker, Harrison; Chagoya, Gus; Davis, Matthew C; Bernstock, Joshua; Omar, Nidal B; Patel, Daxa; Guthrie, Barton
Abstract: INTRODUCTION: Deep brain stimulation (DBS) has become a standard treatment for medically refractory Parkinson's disease (PD), essential tremor and dystonia. Adverse events are rare, and the most common non-hardware complications after DBS include perioperative altered mental status, symptomatic intraparenchymal hemorrhage, and ischemic infarction. Seizures during or after DBS surgery have been reported infrequently. Prior studies report an incidence ranging from 0.4-4% and few studies have reported new-onset DBS-associated epilepsy. METHODS: We performed a single center retrospective case-control study of all DBS implantation procedures from April 1998 to January 2019. The outcome of interest was seizure associated with DBS implantation. Univariate analyses were performed using Student's t-test for parametric continuous outcomes. We used the Kruskal-Wallis test/Wilcoxon rank sum test for nonparametric continuous outcomes, chi-square statistics for categorical outcomes, and multivariate logistic regression for binomial variables. RESULTS: 814 DBS electrode implantations were performed in 645 patients (478 or 58.7% in men and 520 or 63.9% in patients with Parkinson's disease). In total, 23 (2.8%) placements and 22 (3.4%) of patients experienced seizure. Of the 23 DBS-related seizures, 21 were new-onset seizures (3.3% of patients) and 2 were recurrence or worsening of prior seizure disorder. Among the 22 patients with DBS-related seizure, 4 (17.4%) developed epilepsy post-operatively; the risk of DBS-associated epilepsy was 0.50% per DBS placement and 0.63% per patient. Nine (39.1%) of DBS-related seizures had associated post-operative radiographic abnormalities. Multivariate analyses suggested that age at surgery conferred modest increased risk for post-op seizures (OR 1.06, 95% CI 1.02-1.10). Sex, primary diagnosis, electrode location/sidedness, and number of trajectories, were not significantly associated with seizures after DBS surgery. CONCLUSION: DBS-associated seizure is an uncommon occurrence, with an overall observed risk of 2.8% per procedure. The majority of these events occurred within the early post-operative period. Post-DBS epilepsy is an even less common complication, occurring after 0.50% of DBS procedures and in 0.63% of patients. Age at surgery was significantly associated with risk of seizure, while other perioperative variables were not.